Harnessing prebiotic formamide chemistry: a novel platform for antiviral exploration - Maria Grazia Martina; Chiara Vagaggini; Elena Dreassi; Marta De Angelis; Lucia Nencioni; Filippo Dragoni; Federica Giammarino; Adele Boccuto; Maurizio Zazzi; Ilaria Vicenti; Marco Radi (Scientific Reports)
Abstract Viruses and host cells are intricately connected through a shared “chemical language” that may trace back to the prebiotic chemistry of early Earth. In this study, we present an innovative platform for antiviral exploration inspired by this primordial chemical framework. By “doping” the formamide-based prebiotic chemistry model with orotic acid derivatives, we generated complex, non-natural chemical mixtures capable of disrupting the replication of multiple viruses with minimal or no toxicity for eukaryotic cells. This strategy underscores the potential of an evolution-inspired approach in antiviral discovery, offering a novel avenue for identifying new agents with unconventional mechanisms that might elude traditional discovery methods.